INTRODUCTIVE RESOURCES OF MEDICAGO AND PERSPECTIVES OF THEIR APPLICATION IN MOUNTAINOUS CONDITIONS - M. D. Dibirov; E. A. Dzyubenko (Труды по прикладной ботанике, генетике и селекции)
As a result of introductive tests of perennial Medicago species, interspecific differences in a set of traits were revealed. It was found that with the increase of the height above sea level the number of shoots on individual plant increases, while the productivity of shoots and individual plants decreases. Species, varieties and forms promising for Mountainous Dagestan were identified and selected.